Rendimiento y resistencia a la roya (Puccinia spp.) de líneas avanzadas de trigo (Triticum aestivum L) y trigo duro (Triticum turgidum L.) en condiciones de Canchán-Huánuco - Limaylla Jurado, Ruben (2017)
In order to determine the yield and resistance to rust (Puccinia spp) in advanced lines of wheat (Triticum aestivum L.) introduced in terms of Canchan-Huánuco (2 020 m) were evaluated in the 2013 season in 50 lines International Yield Trial (20 SAWYT) using completely randomized design with two replications and 108 lines in the International Selection Nursery (30 SAWSN) with a systematic distribution without repetition. The first experiment, we selected eight promising lines with yields between 3 163.9 6 566.7 kg / ha with answers moderately resistant to rust and a severity equal to or less than 10%. In the second trial were 15 lines identified above, with yields between 1 700 and 4 150 kg / ha with adequate levels of resistance to rust and agronomic rates that encourage high performance.